Daily Symptom Profiles of Children With ADHD Treated With Modified-Release Methylphenidate: An Observational Study. (January 2017) - Hautmann, Christopher; Rothenberger, Aribert; Döpfner, Manfred
Objective : The aim was to identify subgroups of patients with ADHD with different daily symptom profiles and to characterize their response to modified-release methylphenidate (MR MPH) treatment, using data from the observational trial OBSEER.Method : OBSEER included patients aged 6 to 17 years receiving MR MPH under routine care. To detect subgroups, a latent class cluster analysis was applied. Sex, age, MR MPH dose, and emotional symptoms were considered predictors of response.Results : The analysis included 637 patients (81.3% male), with a mean age (standard deviation) of 10.1 (2.5) years. A two-class solution best fit the data, identifying a high-severity group (49.8%) with pronounced symptom reduction, and a low-severity group (50.2%) with minor changes throughout the day. Younger age, male sex, and higher MPH doses were predictive of the high-severity class.Conclusion : Children with ADHD treated with MR MPH are heterogeneous, and subgroups with differential treatment response can be identified.